The Influence of Education and Training on Labor Productivity in Indonesia - Permana, Patricius Danes; Larasati, Lady; Hati, Chelsea Maharani Permata; Amrina, Dania Hellin (Journal of International Conference Proceedings, 2023)
In the reform era, the role of Human Resources (HR) has become increasingly crucial in various institutions, such as government, BUMN, and companies. Education and training are the main steps in efforts to improve the quality and productivity of human resources. Labor productivity is influenced by education and training which can develop knowledge and skills. Good HR management can be an important factor in the operational success of a company. The productivity of labor plays a crucial role in the economic advancement of a region. This research analyzes the influence of education and training on labor productivity in Indonesia, a literature review was employed as the methodology. The findings indicate a positive and substantial correlation between education, training, and labor productivity. The findings of this research can be utilized by the government to comprehend the significance of education and training in initiatives aimed at boosting labor productivity. allocations in the education sector can be increased, including formal education and skills training. The younger generation can also play an active role and take advantage of available educational and training opportunities to improve their knowledge and skills, such as taking courses, educational programs, or training that are relevant to their fields of interest.